2022
DOI: 10.4049/immunohorizons.2200043
|View full text |Cite
|
Sign up to set email alerts
|

Can Infectious Disease Control Be Achieved without Antibiotics by Exploiting Mechanisms of Disease Tolerance?

Abstract: Antimicrobial use in animal agriculture may be contributing to the emerging public health crisis of antimicrobial resistance. The sustained prevalence of infectious diseases driving antimicrobial use industry-wide suggests that traditional methods of bolstering disease resistance are, for some diseases, ineffective. A paradigm shift in our approach to infectious disease control is needed to reduce antimicrobial use and sustain animal and human health and the global economy. Targeting the defensive mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…In spite of the biosecurity strategies and partly due to current systems themselves, the incidence of multifactorial production diseases is persistently high, and this is considered as a sign that the farm animals' ability to adapt to the demanding circumstances and high production output is overstressed (Opriessnig et al, 2011;Sundrum, 2015;Wisnieski et al, 2019). This strongly suggests that important issues that affect the development of diseases are ignored and that additional strategies are required to cope with livestock diseases (Hassan et al, 2022;Knaus, 2009;Lopez, 2022;Nakov et al, 2019;Proudfoot & Habing, 2015;Sundrum, 2015). As the most important issue, it is suggested that little attention has been paid to the animal's capacity to cope with disturbances and that allow them to bounce back to normal functioning after disturbances (Nakov et al, 2019; Saborido & Moreno, 2015; Scheffer et al, 2018).…”
Section: The Relevance Of Animal Resilience In Relation To Diseasesmentioning
confidence: 99%
“…In spite of the biosecurity strategies and partly due to current systems themselves, the incidence of multifactorial production diseases is persistently high, and this is considered as a sign that the farm animals' ability to adapt to the demanding circumstances and high production output is overstressed (Opriessnig et al, 2011;Sundrum, 2015;Wisnieski et al, 2019). This strongly suggests that important issues that affect the development of diseases are ignored and that additional strategies are required to cope with livestock diseases (Hassan et al, 2022;Knaus, 2009;Lopez, 2022;Nakov et al, 2019;Proudfoot & Habing, 2015;Sundrum, 2015). As the most important issue, it is suggested that little attention has been paid to the animal's capacity to cope with disturbances and that allow them to bounce back to normal functioning after disturbances (Nakov et al, 2019; Saborido & Moreno, 2015; Scheffer et al, 2018).…”
Section: The Relevance Of Animal Resilience In Relation To Diseasesmentioning
confidence: 99%